Spectrophotometric Determination of Phenothiazine Drugs with N-iodosuccinimide - Revanasiddappa, H.D.; Shanmukhappa, S. (Asian Journal of Chemistry, 2010)
A simple and rapid spectrophotometric method for the determination of seven phenothiazine derivatives, based on the colour reaction with N-iodosuccinimide is described. The reaction proceeds via oxidation of phenothiazine nucleus into a semiquinonoid radical. The optimum reaction condition and other analytical parameters are evaluated. A study of the effect of commonly associated excipients revealed that they did not cause interference. The new method has been applied for the assay of phenothiazine drugs in pure and dosage form. Statistical comparison of the results with those of an official method shows excellent agreement and indicates no significant difference in precision.